Dampak Teknologi dan kekuatan pasar terhadap Elastisitas Permintaan dan Strategi Penetapan Harga di Marketplace Shopee - Heri Kurniawan; Ummul Madaniah; Abi Puspita Rachmadani; Septian Umar Rizqi; Pupung Purnamasari (CV. ITTC INDONESIA, 2025)
This study aims to analyze the influence of information technology advances and market forces on demand elasticity and pricing strategies on the Shopee marketplace platform. In a highly competitive digital era, the use of technology is not only an operational support tool, but also a strategic instrument to analyze consumer behavior and adjust prices in real-time. This study uses a qualitative approach with a literature study method that examines relevant literature related to e-commerce dynamics, market structure, and price theory. The results show that information technology enables operational efficiency, increased flexibility, and strengthens the relationship between sellers and consumers. Meanwhile, market forces play an important role in determining competitive positions and price elasticity offered. Shopee, as one of the largest e-commerce platforms in Indonesia, is required to continue to innovate in pricing strategies through the use of data and digital features such as promotions and discounts. The integration of technology with an understanding of market structure is proven to improve customer satisfaction, strengthen competitiveness, and maintain market share in a dynamic and ever-evolving e-commerce ecosystem.